THE ROLE AND SIGNIFICANCE OF KNOWLEDGE, EDUCATION AND TRAINING IN ORGANIZATIONS OF THE TOURISM INDUSTRY - Vučković, Jelisaveta (The Business of Tourism, 2024)
In the global labor market, seen in the part that refers to tourism industry, big and fast changes are happening , which as a result have the creation of a large number of new jobs, as well as significant changes or the disappearance of existing jobs. Therefore, the necessity of permanent lifelong education and training of employees is imposed, in order to improve existing knowledge (upskilling) or necessary reskilling.The subject of analysis in this paper are factors which determine role and significance of education and training in organizations of the tourism industry, goals of education and training in organizations of the tourism industry, phases, characteristics and benefits of education and training, as well as adults learning theory and principles.
Keywords: employees; education; training; organizations of the tourism industry